DIRAS2 Is a Prognostic Biomarker and Linked With Immune Infiltrates in Melanoma - Xue, Wenli; Zhu, Hongbo; Liu, Hongye; He, Hongxia (Frontiers in Oncology, 2022)
Background: Skin cutaneous melanoma (SKCM) is a highly malignant skin tumor. There is evidence that DIRAS2 is a tumor suppressor gene, but its role in SKCM has not been studied. Methods: We implemented Gene Expression Profiling Interactive Analysis (GEPIA) to investigate the expression of DIRAS2 in SKCM, and plotted the survival curve to determine the effect of DIRAS2 on the survival rates of SKCM patients. Then, we also discussed the correlation between DIRAS2 and tumor immune infiltration, and determined the expression of DIRAS2 and immune infiltration level in SKCM immune cells using TIMER. The top 100 genes most associated with DIRAS2 expression were used for functional enrichment analysis. In order to confirm the anti-cancer effects of DIRAS2 in SKCM in the data analysis, we conducted in vitro assays as well as in vivo studies of DIRAS2 on SKCM tumour cell proliferation, migration, invasion and metastasis. Western blot and immunofluorescence assay were empoyed to study the relationship between DIRAS2 and Wnt/β-catenin signaling pathway in SKCM. Results: Univariate logistic regression analysis showed that DIRAS2 expression was significantly correlated with tumor grade. Multivariate analysis manifested that DIRAS2 was an independent prognostic factor for SKCM. Of note, DIRAS2 expression levels were positively correlated with the infiltration levels of B cells, CD4+ T cells and CD8+ T cells in SKCM. The infiltration of B cells, CD4+ T cells and CD8+ T cells was positively correlated with the cumulative survival rate of SKCM patients. In vitro experiments suggested that proliferation, migration, invasion and metastasis of SKCM tumor cells were distinctly enhanced after DIRAS2 knockdown. Furthermore, depletion of DIRAS2 promoted melanoma growth and metastasis in vivo. As for the mechanism, silencing DIRAS2 can activate the signal transduction of the Wnt/β-catenin signaling pathway. Conclusion: DIRAS2 is a tumor suppressor gene in cases of SKCM through restraining the Wnt/β-catenin signaling and is also associated with immune infiltration in SKCM.